Clinical implications of m6A‐related regulators YTHDF1 and YTHDF2 in hepatocellular carcinoma - Nanfang Qu; Xuemei Zhang; Xianbin Wu; Xia Zhou; Zhejun Deng; Lei Ma; Yanhua Liu; Wenhong Ge; Huanghuang Jiang; Longkuan Xu; Haixing Jiang (Precision Medical Sciences, 2022)
Abstract It aims to examine the correlation between the expression of YTHDF1 and YTHDF2 and the clinical, pathological, and prognostic factors in HCC. The study was done using statistics from TCGA to establish the noted relationship. The degree of YTHDF1 and YTHDF2 protein expression in 88 HCC as well as the adjacent tissues was then determined through IHC examination, and we examined how that expression linked with other clinicopathological traits and clinical outcomes. Bioinformatics examination revealed that YTHDF1 and YTHDF2 expression was increased in HCC tissues, and poor pathology grade and prognosis were linked to high expression. YTHDF1 protein expression in IHC was notably higher in HCC tissue (p = .023). It was associated with age (p = .002) but not with other clinicopathological characteristics or prognoses. When compared to paraneoplastic tissues, the expression of the protein YTHDF2 was considerably higher in HCC tissues (p < .0001); and its high expression due to worse pathological grading (p = .035), higher alpha fetoprotein expression (p = .04), higher tumor recurrence (p = .023), lower overall survival rate (p = .011), and lower recurrence free survival rate (p = .005). A separate predictive factor for determining recurrence‐free survival in HCC was YTHDF2. A novel molecular marker called YTHDF2 may be used to assess HCC patients' prognoses.